Instagram Reels, Influencer Credibility, and Halal Cosmetic Purchase Decisions - Aliva, Aliya Vika; Indra, Ricardo; Aras, Muhammad (Universitas prof. Dr. Moestopo (Beragama), 2026)
This study aims to examine the influence of Instagram Reels and influencer credibility on purchase decisions in Indonesia’s halal cosmetics market, with brand awareness serving as a mediating variable. A quantitative research approach was employed using an online survey of 400 Indonesian Instagram users who follow halal cosmetic brands and have prior purchasing experience. The data were analyzed using structural equation modeling with a partial least squares (PLS-SEM) approach to evaluate both direct and indirect relationships among variables. The findings indicate that Instagram Reels significantly influence brand awareness and purchase decisions, highlighting the persuasive role of visually engaging short-form video content. Influencer credibility significantly enhances brand awareness, while its effect on purchase decisions occurs indirectly through brand awareness. These results demonstrate the important role of brand awareness in translating digital engagement into purchasing behavior. This study contributes to the digital marketing communication literature by clarifying how short-form video content and influencer credibility interact to shape consumer decision-making and provides practical insights for developing effective marketing strategies in halal-oriented markets.